Optical performance of finished and unfinished tropical timbers exposed to ultraviolet light in the field in Costa Rica. Issue 2 (14th March 2016) - Salas, Cynthia; Moya, Róger; Vargas-Fonseca, Lupita
Abstract: This study evaluated wood color change (Δ E* ) and the surface quality in 10 tropical wood species painted with three finishes (composed of wax and polyurethane). Two weathering conditions were tested: natural weathering (NW) and artificial weathering (AW). The results showed that the application of these finishes, decreased the luminosity ( L *), increased the redness ( a *) and the yellowness ( b *) parameters in all species. Δ E *, after weathering exposure, was affected significantly by L *, a *, and b, whereas for finished or pretreated wood, L * and b * are the main parameters affecting Δ E * in the 10 tropical species studied. Δ E * values found in different finishes and pretreatments are cataloged as total change of color. Other important results were that tropical light colored timber with natural pretreatment produced higher Δ E * than dark colored timber. The stains and fungal development were observed in polyurethane finishes in NW, but not in AW. The irregular and mosaic flaws were not observed in any kind of finish or pretreatment of surface. The values of the quality index created, which considered long and short lines and switch flaws, were lowest in NW and in waxy finish, while the highest value was obtained with the polyurethane finish.